Buddhist Concepts as Implicitly Reducing Prejudice and Increasing Prosociality. (April 2015) - Clobert, Magali; Saroglou, Vassilis; Hwang, Kwang-Kuo
Does Buddhism really promote tolerance? Based on cross-cultural and cross-religious evidence, we hypothesized that Buddhist concepts, possibly differing from Christian concepts, activate not only prosociality but also tolerance. Subliminally priming Buddhist concepts, compared with neutral or Christian concepts, decreased explicit prejudice against ethnic, ideological, and moral outgroups among Western Buddhists who valued universalism (Experiment 1, N = 116). It also increased spontaneous prosociality, and decreased, among low authoritarians or high universalists, implicit religious and ethnic prejudice among Westerners of Christian background (Experiment 2, N = 128) and Taiwanese of Buddhist/Taoist background (Experiment 3, N = 122). Increased compassion and tolerance of contradiction occasionally mediated some of the effects. The general idea that religion promotes (ingroup) prosociality and outgroup prejudice, based on research in monotheistic contexts, lacks cross-cultural sensitivity; Buddhist concepts activate extended prosociality and tolerance of outgroups, at least among those with socio-cognitive and moral openness.